Initial clinical experience with a radiation oncology dedicated open 1.0T MR‐simulation. (8th March 2015) - Glide‐Hurst, Carri K.; Wen, Ning; Hearshen, David; Kim, Joshua; Pantelic, Milan; Zhao, Bo; Mancell, Tina; Levin, Kenneth; Movsas, Benjamin; Chetty, Indrin J.; Siddiqui, M. Salim
Abstract : The purpose of this study was to describe our experience with 1.0T MR‐SIM including characterization, quality assurance (QA) program, and features necessary for treatment planning. Staffing, safety, and patient screening procedures were developed. Utilization of an external laser positioning system (ELPS) and MR‐compatible couchtop were illustrated. Spatial and volumetric analyses were conducted between CT‐SIM and MR‐SIM using a stereotactic QA phantom with known landmarks and volumes. Magnetic field inhomogeneity was determined using phase difference analysis. System‐related, in‐plane distortion was evaluated and temporal changes were assessed. 3D distortion was characterized for regions of interest (ROIs) 5 – 20   cm away from isocenter. American College of Radiology (ACR) recommended tests and impact of ELPS on image quality were analyzed. Combined ultrashort echotime Dixon (UTE/Dixon) sequence was evaluated. Amplitude‐triggered 4D MRI was implemented using a motion phantom (2–10 phases, ~ 2   cm excursion, 3–5 s periods) and a liver cancer patient. Duty cycle, acquisition time, and excursion were evaluated between maximum intensity projection (MIP) datasets. Less than 2% difference from expected was obtained between CT‐SIM and MR‐SIM volumes, with a mean distance of < 0.2   mm between landmarks. Magnetic field inhomogeneity was < 2   ppm . 2D distortion was < 2   mm over 28.6 – 33.6   mm of isocenter. Within 5 cm radius of isocenter, mean 3D geometric distortion was 0.59 ± 0.32   mm ( maximum = 1.65   mm ) and increased 10 – 15   cm from isocenter ( mean = 1.57 ± 1.06   mm, maximum = 6.26   mm ). ELPS interference was within the operating frequency of the scanner and was characterized by line patterns and a reduction in signal‐to‐noise ratio (4.6–12.6% for TE = 50 − 150   ms ). Image quality checks were within ACR recommendations. UTE/Dixon sequences yielded detectability between bone and air. For 4D MRI, faster breathing periods had higher duty cycles than slow (50.4% (3 s) and 39.4% (5 s), p < 0.001 ) and ~ fourfold acquisition time increase was measured for ten‐phase versus two‐phase. Superior–inferior object extent was underestimated 8% (6 mm) for two‐phase as compared to ten‐phase MIPs, although < 2 % difference was obtained for ≥ 4 phases. 4D MRI for a patient demonstrated acceptable image quality in ~ 7   min . MR‐SIM was integrated into our workflow and QA procedures were developed. Clinical applicability was demonstrated for 4D MRI and UTE imaging to support MR‐SIM for single modality treatment planning. PACS numbers: 87.56.Fc, 87.61.‐c, 87.57.cp